Electrical Conductivity Effect on the Performance Evaluation of Eit Systems: A Review - Sepulveda-Palma, F (Elsevier B.V., 2021)
Electrical Impedance Tomography (EIT) is a non-invasive technique in the study for flow measurement of multiphase flow. Its high temporal resolution allows achieving images of the flow in real-time. In oil extraction, the demand for deepwater requires research and technologies capable of predicting the influence of the saline water s high conductivities in control systems. In this technique (EIT), most studies focus on low conductivities (from tap water). Therefore, this work s objective was to identify the effects of conductivity in the performance evaluation of systems in EIT. For that matter, a systematic review is conducted utilizing the Multiple Criteria Decision Analysis method (MCDA) to classify the works selected in the search. © 2021